Mammary tumors expressing the neu proto-oncogene possess elevated c-Src tyrosine kinase activity. - Muthuswamy, S K (1994)
Amplification and overexpression of the neu (c-erbB2) proto-oncogene has been implicated in the pathogenesis of 20 to 30% of human breast cancers. Although the activation of Neu receptor tyrosine kinase appears to be a pivotal step during mammary tumorigenesis, the mechanism by which Neu signals cell proliferation is unclear. Molecules bearing a domain shared by the c-Src proto-oncogene (Src homology 2) are thought to be involved in signal transduction from activated receptor tyrosine kinases such as Neu. To test whether c-Src was implicated in Neu-mediated signal transduction, we measured the activity of the c-Src tyrosine kinase in tissue extracts from either mammary tumors or adjacent mammary epithelium derived from transgenic mice expressing a mouse mammary tumor virus promoter/enhancer/unactivated neu fusion gene. The Neu-induced mammary tumors possessed six- to eightfold-higher c-Src kinase activity than the adjacent epithelium. The increase in c-Src tyrosine kinase activity was not due to an increase in the levels of c-Src but rather was a result of the elevation of its specific activity. Moreover, activation of c-Src was correlated with its ability to complex tyrosine-phosphorylated Neu both in vitro and in vivo. Together, these observations suggest that activation of the c-Src tyrosine kinase during mammary tumorigenesis may occur through a direct interaction with activated Neu.